Evaluation and prediction of high-quality development in China: A time-spatial analysis from Hubei province - Huang, Jin; Tian, Ye; Khanal, Ribesh; Wen, Faguang; Deng, Chaohui (Frontiers in Environmental Science, 2022)
High-quality sustainable development is the common goal pursued by all countries in the world. China’s high-quality development (HQD) includes five concepts of “innovation, coordination, green, opening-up, and sharing”. In this context, we established an evaluation system that included these five fundamental characteristics, used the comprehensive entropy method and BP neural network to evaluate and predict the high-quality development of Hubei Province in China, and conducted a spatiotemporal deductive analysis. The study found that: 1) Economic growth still has an important impact on HQD, for all the five main indicators, “opening-up” and “innovation” have the highest impact weights, which are 0.379 and 0.278, respectively, while the proportions of coordination and sharing are both less than 0.1. 2) There are huge differences in the level of high-quality development between regions in Hubei Province. From 2010 to 2020, the average comprehensive index of Wuhan City was greater than 0.5, which is 7 times that of the second Xiangyang City, and 46 times that of the last Shennongjia district. 3) In the past few years, the overall high-quality development of Hubei Province has shown a fluctuating upward trend. However, due to the impact of COVID-19, during the following years, its comprehensive development index will decline by an average of 5% annually, but starting from 2022, it will gradually increase. As a result, tailored and coordinated sustainable environmental policies of integrating institutional and open-market measures should be provided.